High Bowel Perforation Due Closed Abdominal Trauma in Patient with Chronic Desnutrition and Turner Syndrome. Clinical Case - Flores-López, Alejandro Alberto; Falcón-Cancino, Luis Arturo; Carrillo-Pinto, Laura Daniela Caridad; Espinosa-Rosales, Alicia Valeria; Cáceres-Moreno, Cristóbal Aldair; Echevarría-Fernández, Fidel; García-Flores, Rubén; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Surgical emergencies continue to be a public health problem it is estimated that 5 billion people around the world do not have access to surgery when they need it, particularly in the context of an emergency, this is even more true in countries of low economic income, low political culture and poor per capita distribution of national income, where nine out of ten people do not have access to basic surgical care. Clinical case: A 46-year-old female was admitted to the emergency department due to dyspnea and abdominal pain. She begins 7 days before her admission, with a fall from the stairs of her home. When she was admitted, she had a blood pressure of 60/40 mmHg, and significant abdominal distension, for which she began management with noradrenaline, Acute Kidney Injury was documented. A Simple Abdominal Computed Tomography was performed, which reported: Pancreas increased in size at the level of the head, peripancreatic heterogeneous collection, and free fluid in the abdominal cavity 7000 mL; Exploratory laparotomy was performed, which found: abundant purulent and intestinal fluid in the cavity, perforation of 50% of the intestinal lumen at 12 cm and denuding of the serosa at 60 cm from the angle of Treitz, pancreatic tumor; the abdominal cavity is cleaned, a pancreatic biopsy is taken. During her hospital stay, she was managed with broad-spectrum antibiotics, Parenteral Nutrition, she presented metabolic pancreatitis due to TPN 4 days after treatment, Upper Digestive Tract Bleeding that required transfusions; she began an enteral liquid diet, progressed towards improvement until her hospital discharge 19 days after surgery. The histopathological report of pancreatic biopsy reported inflammatory tissue. Discussion: Trauma patients may visit the emergency department on foot, in private vehicles, or via an emergency medical service. In Japan, ambulances are available to everyone free of charge, and the telephone triage system recommends that patients with minor injuries go to the emergency department on their own and those with serious injuries use the Emergency Medical Service.